2016
DOI: 10.1186/s40064-016-1794-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic inhibition of meloxicam by specific CYP2C9 inhibitors in Cunninghamella blakesleeana NCIM 687: in silico and in vitro studies

Abstract: Specific inhibitors of Cytochrome P4502C9 enzyme (CYP2C9) viz. clopidogrel, fenofibrate fluvoxamine and sertraline at concentration of 50, 100, 150 and 200 µM were employed to investigate the nature of enzyme involved in bioconversion of meloxicam to its main metabolite 5-OH methyl meloxicam by Cunninghamella blakesleeana. Virtual screening for interaction of specific CYP2C9 inhibitors with human CYP2C9 enzyme was performed by molecular docking using Auto dock vina 4.2 version. The in silico studies were furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Meloxicam is highly metabolized, with cytochrome P4502C9 enzyme (CYP2C9) being the main enzyme responsible for the drug metabolism with a small contribution from cytochrome P4503A4 enzyme (CYP3A4). Almost 60% of the ingested dose is metabolized to its major metabolite, 5′-carboxymeloxicam, from an oxidation of liver cytochrome enzymes to an intermediate metabolite, 5′-hydroxymethylmeloxicam [ 6 , 7 , 8 , 9 , 10 , 11 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meloxicam is highly metabolized, with cytochrome P4502C9 enzyme (CYP2C9) being the main enzyme responsible for the drug metabolism with a small contribution from cytochrome P4503A4 enzyme (CYP3A4). Almost 60% of the ingested dose is metabolized to its major metabolite, 5′-carboxymeloxicam, from an oxidation of liver cytochrome enzymes to an intermediate metabolite, 5′-hydroxymethylmeloxicam [ 6 , 7 , 8 , 9 , 10 , 11 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meloxicam is highly metabolized, with cytochrome P4502C9 enzyme (CYP2C9) being the main enzyme responsible for the drug metabolism with a small contribution from cytochrome P4503A4 enzyme (CYP3A4). Almost 60% of the ingested dose is metabolized to its major metabolite, 5 -carboxymeloxicam, from an oxidation of liver cytochrome enzymes to an intermediate metabolite, 5 -hydroxymethylmeloxicam [6][7][8][9][10][11] (Figure 1). Recent studies have demonstrated that allelic variations in CYP2C9 are related to the increase in the adverse events induced by non-steroidal anti-inflammatory drugs (NSAIDs), including meloxicam.…”
Section: Introductionmentioning
confidence: 99%